New records of bats (Chiroptera, Mammalia) from Argentina - Gamboa Alurralde, Santiago (2016)
We provide new distributional records for five species of bats from Argentina, of the families Vespertilionidae and Molossidae, representing new records for Catamarca, Chaco, La Rioja, Misiones, and San Juan provinces, as well as unpublished data for several phytogeographic regions of the country. This information adds important extensions to the distribution of Eumops glaucinus (Wagner, 1843) in Argentina.